DISASTER RISK REDUCTION STRATEGY BASED ON INTEGRATION EARTHQUAKE RISK ASSESSMENT WITH SPATIAL PLANNING BASED ON MICROZONATION IN TASIKMALAYA CITY, WEST JAVA - Alcanadre Tanjung Moechtar, Rio
The West Java area, especially Tasikmalaya, is geologically prone to earthquakes. However, spatial planning in city-level planning documents must still accommodate earthquake mitigation efforts. In addition, Tasikmalaya City itself also has a high population because it is an area with potential for tourism, education, and trade. Urban areas need to plan spatial planning on a micro-scale basis. Earthquake microzonation can be integrated into planning documents in spatial planning as an effort to reduce earthquake risk. This study identifies earthquake risk areas on a micro-scale and integrates them into the spatial structure and patterns in the City of Tasikmalaya. From the results of the study, it was found that Tasikmalaya City was divided into three classes, namely SC (low threat), SD (moderate threat), and SE (high threat). Areas with a high hazard threat are in parts of the SPK and several areas in the PPK. The moderate threat of earthquakes dominates most of the Tasikmalaya City area. Based on earthquake risk analysis, the area with high risk is 4502 hectares. This is relatively high compared to the total high hazard of 957 hectares. The area with the broadest high risk is the Kawalu District area. This is due to low capacity in the form of no evacuation sites and health facilities. In addition, high economic and physical vulnerability also causes a large area of high risk. In an effort to reduce disaster risk, it is necessary to carry out Earthquake-resistant buildings, such as construction, following the rules of the building code. In addition, there is also a need to increase capacity in evacuation sites, such as creating green open spaces and health facilities in areas that have a high threat and risk of earthquakes.